Analisis Prosedur Pengadaan Bahan Makanan terhadap Tingginya Food Cost di Hotel FPS Bali - Komang Ari Suryantini; Ida Ayu Kalpikawati; I Nyoman Sukana Sabudi (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
The food procurement procedure plays a crucial role in hotel operations as it directly impacts the food cost value. An excessive food cost above the standard indicates inefficiency that needs to be addressed through an analysis of the procurement process. This study was conducted at Hotel FPS Bali Ungasan with the aim of understanding how the food procurement procedure contributes to high food costs. The research used a qualitative approach with data collection techniques through in-depth interviews with four informants: Jr. Accountant, Purchasing Supervisor, Receiving Staff, and Cost Control Staff. The informants were selected using purposive sampling based on their roles in the food procurement process. The findings revealed that the procurement process has not been running optimally. Some issues identified include orders not always matching the actual needs, the receipt of goods without thorough quality checks, and food storage not fully complying with the established standards. These discrepancies have led to high food costs, which averaged 36.70% in 2024, exceeding the set standard of 34.58%. This indicates that inconsistent implementation of the food procurement procedure is one of the main factors contributing to the increased food cost at the hotel. Therefore, to reduce food costs and improve operational efficiency, the hotel needs to ensure that the procurement procedures are followed more consistently, from planning the required food items, inspecting the quality of received goods, to storage practices that comply with the standards.